If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5b = -10 + 6b Solving 5b = -10 + 6b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-6b' to each side of the equation. 5b + -6b = -10 + 6b + -6b Combine like terms: 5b + -6b = -1b -1b = -10 + 6b + -6b Combine like terms: 6b + -6b = 0 -1b = -10 + 0 -1b = -10 Divide each side by '-1'. b = 10 Simplifying b = 10
| 28x+11=1 | | 2y^3=0 | | 7x+5=9z-5 | | 8v=-344 | | k+-15k+7=-7 | | 5b=200 | | 6cos(x)-4=0forx | | 6*cos(x)-4=0 | | x^2+px-9=(x-1)(x+q) | | -5t+12t+9t=-16 | | 8v(8v)= | | 2x^2+10x+30= | | 3f-8=6f+10 | | 28=2(-6+x) | | 5x+mk=7k | | 2(2x+3)-4=2x+5 | | -2(r+7)=14 | | 2x^2+12x+30= | | 4+4s=-8 | | -12/s=4 | | 2+(15)x=-7 | | 7-5x=10-(6x-7) | | 4x(x-12)=20 | | 2+3b=c | | 7r-15=3r+21 | | -6(8f+3)=26-7f | | m3-7=-10 | | 6-2(x-3)+4=4(2-3x) | | 12=-2-4 | | 7y+6x=6 | | -9a+45=-18 | | 3xsquared-24x+45=0 |